The Impact of Financial Literacy and Inclusion on MSME Performance in Talang Babat: An Empirical Approach to Driving Local Economic Growth - Agung Prayoga, Dimas; Abidin, Zaenal; Yatima, Khusnul; Musthofa , M. Arif; Kartika Devi, Erwina; Okva Marwendi, Reza (CV. Civiliza Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet their performance in regions like Talang Babat Subdistrict remains suboptimal due to low financial literacy and limited financial inclusion. This study investigates the individual and simultaneous effects of financial literacy and financial inclusion on MSME performance using a quantitative causal approach with multiple linear regression analysis. Data were collected from 89 MSME actors selected through cluster random sampling. The results demonstrate that both financial literacy and financial inclusion significantly and positively influence MSME performance, explaining 68.8% of its variance. The study highlights the synergistic impact of these variables, emphasizing the importance of integrating financial education with improved access to formal financial services. Findings also underscore the practical importance of separating personal and business finances and structured financial record-keeping in enhancing business sustainability. The study contributes to MSME literature by providing an integrative model and offers policy recommendations for local governments and financial institutions to support MSME development through holistic financial capacity building and inclusion strategies